Bathyal polychaete assemblages in the region of the Subtropical Front, Chatham Rise, New Zealand - P. K. Probert; C. J. Glasby; S. L. Grove; B. L. Paavo (New Zealand Journal of Marine and Freshwater Research, 2009)
Polychaetes were collected from eight sites across the Chatham Rise (New Zealand) in the region of the Subtropical Front from water depths of c. 2300 m to 350 m. A total of 169 putative species representing 36 families was identified. Spionidae, Paraonidae, Cirratulidae, Syllidae, and Orbiniidae accounted for 50% of all polychaete individuals. Multivariate analysis revealed that three sites at c. 350–453 m water depth on muddy sand (6–7% clay) shared similar faunal and environmental characteristics. Numerical dominants included Lumbrineris sp., P seudeurythoe minuta, Dipolydora cf. socialis, Aglaophamus verrilli, Prionospio lehlersi , Syllinae sp., Monticellina sp., and Cossura sp. Replicates from a single site at c. 750 m depth on the southern flank of the Rise produced a distinct assemblage dominated by Paradoneis, Naineris, Notomastus , Harmothoinae, Prionospio lehlersi, Levinsenia, Aricidea, Kebuita, Paraonella , and ? Leiochrus species. Replicates from greater depths north and south of the Rise presented a greater range of assemblage characteristics and environmental parameters including temperature, dissolved oxygen, median grain size, calcium carbonate (CaCO 3 ), and total organic matter content. Twenty‐eight taxa were found exclusively below 750 m depths including species of Ampharetinae, Chloeia, Pseudeurythoe , Capitellidae, and Cirratulidae. There was a significant difference in faunal composition between northern and southern flanks of the Rise within depth classes and also between sites at the same depth classes. Faunal density and species diversity appeared highest from the crest to 750 m depth on the southern side. Low species diversity at the deepest sites may be confounded by reduced density.

Trophic ecology of coral reef gobies: interspecific, ontogenetic, and seasonal comparison of diet and feeding intensity - V. Hernaman; P. K. Probert; W. D. Robbins (Marine Biology, 2009)

Spatial and temporal patterns of abundance of coral reef gobies (Teleostei: Gobiidae) - V. Hernaman; P. K. Probert (Journal of Fish Biology, 2008)
This study investigated the spatial and temporal patterns of abundance of four substratum‐associated species of Gobiidae on a heterogeneous reef flat comprised of four distinct habitat zones, and examined microhabitat use within each zone. Asterropteryx semipunctatus had the widest distribution and was the most abundant species in each habitat zone, followed by Amblygobius bynoensis , Valenciennea muralis and Amblygobius phalaena . Significant temporal and spatial differences in mean density were evident. The highest density of A. semipunctatus (312 individuals 10 m –2 ) was recorded in a habitat zone dominated by algal‐covered rubble, whereas A. bynoensis and V. muralis were most abundant (mean summer density 5·5–5·8 individuals 10 m –2 ) in habitats containing both sand and hard substrata. In contrast, A. phalaena was uncommon (mean density ≤ 0·4 individuals 10 m –2 ) in all four habitat zones. Significant seasonal differences in abundance were due to the large influx of recruits in summer. Ontogenetic shifts in habitat use were not evident at either the macrohabitat ( i.e. among habitat zones) or microhabitat scale ( i.e. substratum use within zones). At the microhabitat scale, V. muralis consistently exhibited a strong positive association with sand and was rarely associated with hard substrata. In contrast, the two Amblygobius species were commonly associated with both sand and hard substrata, but patterns of microhabitat use differed among habitat zones. Substratum composition at the microhabitat scale may influence spatial patterns of abundance at larger spatial scales by providing essential resources and, or influencing carrying capacity and predation risk.

Macrobenthic polychaete assemblages of the continental shelf and upper slope off the west coast of the South Island, New Zealand - P. K. Probert; G. B. Read; S. L. Grove; A. A. Rowden (New Zealand Journal of Marine and Freshwater Research, 2001)
Polychaete assemblages are described from replicate box‐core samples collected in summer 1983 at 18 stations on the continental shelf and upper slope (28–943 m) off the west coast of the South Island, New Zealand, south‐eastern Tasman Sea (c. 41–43°S, 169–172°E). Three main station groupings were identified by multivariate analysis: (1) inner shelf sandy stations characterised by Prionospio australiensis, Aricidea (Acesta) sp., Magelona cf. dakini, Paraprionospio aff. pinnata, Aglaophamus sp., Heteromastus filiformis , and Magelona sp.; (2) middle to outer shelf muddy stations characterised by Levinsenia cf. gracilis, Prionospio australiensis, Paraprionospio coora, Aglaophamus verrilli , and Auchenoplax mesos; and (3) upper slope sandy mud or mud stations characterised by Prionospio ehlersi . A combination of water depth and sediment clay content provided the best correlation with the biotic pattern. Spionidae was the most abundant family (49% of polychaete individuals), which may reflect the scope for opportunistic species in a shelf environment characterised by a high input of terrigenous sediment and episodic upwelling.

Epibenthic communities on the Chatham Rise, New Zealand - D. G. McKnight; P. K. Probert (New Zealand Journal of Marine and Freshwater Research, 1997)
Samples of epibenthic macrofauna were collected using a small sledge trawl from 40 stations on the Chatham Rise (42°34′‐44°47′S; 175°34′E‐179°03′W) at water depths of 237–2039 m. 218 taxa were collected, predominantly echinoderms, crustaceans, and molluscs. Multivariate analysis based on 85 species indicated three epibenthic communities, the shallowest characterised mainly by crustaceans and two deeper water communities mainly characterised by echinoderms: (1) a community on predominantly sandy sediments on the crest and shallower flanks of the Rise at 237–602 m that included as characteristic species Munida gracilis, Phylladiorhynchus pusillus, Campylonotus rathbunae, Pontophilus acutirostris , and Acutiserolis bromleyana (Crustacea), Amphiura lanceolata (Ophiuroidea), Cuspidaria fairchildi , and Euciroa galatheae (Bivalvia); (2) a community associated with muddy sediments at 462–1693 m that included Ypsilothuria bitentaculata and Pentadactyla longidentis (Holothuroidea), Brissopsis oldhami (Echinoidea), and Amphiophiura ornata (Ophiuroidea); and (3) a community on muddy sediments at 799–2039 m that included Ophiomusium lymani (Ophiuroidea), Porcellanaster ceruleus (Asteroidea), Gracilechinus multidentatus (Echinoidea), and Aeneator recens (Gastropoda). Bathymetric range of the communities was not symmetrical on either side of the Rise; there was a marked submergence on the north side similar to the vertical displacement of the core of the Antarctic Intermediate Water.